Information order effects in clinical psychological diagnoses. (9th March 2017) - Cwik, Jan Christopher; Margraf, Jürgen
Abstract : Despite the wide application and long history of diagnostic systems, several sources of diagnostic errors remain in the criterion‐based diagnosing of mental disorders. The aim of this study was to investigate whether the presentational order of diagnosis‐relevant information and pretreatment reports predict diagnostic errors. One hundred twenty psychotherapists participated in the present online study. The study employed a 2 (symptom presentation: core symptoms at vignette's beginning vs. core symptoms at the end of the case vignette) × 2 (pretreatment report: receiving a pretreatment report with an incongruent diagnosis to the case vignette vs. receiving no pretreatment report) between‐subjects experimental design, with random assignment. Participants were asked to make diagnoses after reading three case vignettes describing patients with different disorder constellations. Additionally, participants rated their confidence in the diagnoses and their estimation of the severity of each diagnosed condition. Results indicated that order of symptom descriptions predicted the correctness of diagnostic decisions, with a recency effect causing more fully correct diagnostic decisions in cases where diagnostic information was presented last. Receiving incongruent pretreatment reports was predictive for diagnostic errors. In conclusion, the results of this study indicate that diagnoses of mental disorders can depend on the way symptoms are presented or reported. Key Practitioner Message: Therapists' diagnostic decisions are not influenced by pretreatment reports. Diagnostic decisions are affected by information order effects. Diagnostic accuracy of psychotherapists is debatable. High rate of misdiagnoses in case vignette with comorbid disorders.